Show me the evidence : mobilisation, citizenship and risk in Indian asbestos issues - Waldman, Linda (Brighton, 2009)
"This paper examines asbestos issues, mobilisation and citizenship in India. It shows how asbestos has been considered as a tool for Indian economic growth and modernisation and explores the scientific debates around its ‘safe’ use. In seeking to locate experiences of citizenship within a globalised context, this research has focused on anti-asbestos mobilisation and protest in cosmopolitan cities as well as more decentralised contexts. It argues that the state’s narrow definition of asbestos diseases enables it to officially document the lack of asbestos diseases experienced by Indian workers. This process, which defines sufferers as politically invisible and inconsequential, accompanied by the 30 year delay between exposure and the onset of disease, hinders anti-asbestos organisations as there is no constituency to be mobilised. Parallel (and partially interrelated) grassroots asbestos movements which are more worker-orientated are, however, marginalised from the transnational protests. The paper argues that mobilisation around identity issues thus creates different contexts in India, in which activists are simultaneously both intimately connected and enormously distant to different aspects of the mobilisation process. In addition, while geographic and political differences are compressed through transnational mobilisation; class, regional and educational differences are expanded."